1965
DOI: 10.1115/1.3678270
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Turbomachinery From Self-Excited Rotor Whirl

Abstract: Aerodynamic exciting forces have caused severe rotor whirl of axial compressors and turbines. One disturbing force investigated is due to circumferential variation of static pressure acting on the cylindrical surface of rotor, particularly within labyrinth seals. Another aerodynamic disturbing force is due to eccentricity of rotor causing circumferential variation of blade-tip clearance, and a corresponding variation of local efficiency and unbalanced torque. Seal deflection criteria and torque deflection crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(91 citation statements)
references
References 0 publications
0
88
0
Order By: Relevance
“…The later coefficients are added to the mechanical system, that is, (2). The polar inertia of the mechanical system is J P = 1.57 Nms 2 , the damping is C = 0 Nms, and the stiffness is K = 49000 Nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The later coefficients are added to the mechanical system, that is, (2). The polar inertia of the mechanical system is J P = 1.57 Nms 2 , the damping is C = 0 Nms, and the stiffness is K = 49000 Nm.…”
Section: Resultsmentioning
confidence: 99%
“…He suggested an analytical model of destabilising forces due to nonsymmetric clearance in steam turbines. Alford [2] developed a similar model for compressors, where the forces are obtained as a function of the change in efficiency due to increased eccentricity. Urlichs [3] carried out the first research in a test rig and suggested corrections to Thomas and Alford's models.…”
Section: Introductionmentioning
confidence: 99%
“…This unsymmetry indicates that the rotor is potentially unstable as described by Black (1) and Alford (2). Depending on the strength of the tangential friction cross-coupling force, acting opposite to the spin direction, the rotor can go unstable very abruptly in a backward precession in some systems, while in others it may act as a deflection limiter.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Self-induced vibrations are caused by forces controlled by the motion itself as opposed to forced vibration which is a function of only time (Boeker and Sternlicht, 1956). Such whirling motion may be caused by external factors such as internal damping (Gunter, 1966), hydrodynamic forces in fixed geometry journal bearings (Reddi and Trumpler, 1962;Newkirk and Taylor, 1925), or oil seals (Kirk and Miller, 1979 (Alford, 1965) as well as centrifugal compressors (Wachel, 1982;Sood, 1979). Subsynchronous vibration in centrifugal compressors may occur in high gas pressures and gas densities applications beyond certain operating conditions and speeds.…”
mentioning
confidence: 99%